Time-domain filtered-x-Newton narrowband algorithms for active isolation of frequency-fluctuating vibration. (14th April 2016) - Li, Yan; He, Lin; Shuai, Chang-geng; Wang, Fei
Abstract: A time-domain filtered-x Newton narrowband algorithm (the Fx-Newton algorithm) is proposed to address three major problems in active isolation of machinery vibration: multiple narrowband components, MIMO coupling, and amplitude and frequency fluctuations. In this algorithm, narrowband components are extracted by narrowband-pass filters (NBPF) and independently controlled by multi-controllers, and fast convergence of the control algorithm is achieved by inverse secondary-path filtering of the extracted sinusoidal reference signal and its orthogonal component using L × L numbers of 2nd-order filters in the time domain. Controller adapting and control signal generation are also implemented in the time domain, to ensure good real-time performance. The phase shift caused by narrowband filter is compensated online to improve the robustness of control system to frequency fluctuations. A double-reference Fx-Newton algorithm is also proposed to control double sinusoids in the same frequency band, under the precondition of acquiring two independent reference signals. Experiments are conducted with an MIMO single-deck vibration isolation system on which a 200 kW ship diesel generator is mounted, and the algorithms are tested under the vibration alternately excited by the diesel generator and inertial shakers. The results of control over sinusoidal vibration excited by inertial shakers suggest that the Fx-Newton algorithm with NBPF have much faster convergence rate and better attenuation effect than the Fx-LMS algorithm. For swept, frequency-jumping, double, double frequency-swept and double frequency-jumping sinusoidal vibration, and multiple high-level harmonics in broadband vibration excited by the diesel generator, the proposed algorithms also demonstrate large vibration suppression at fast convergence rate, and good robustness to vibration with frequency fluctuations.